1995
DOI: 10.1099/0022-1317-76-6-1409
|View full text |Cite
|
Sign up to set email alerts
|

Sodium valproate, an anticonvulsant drug, stimulates human cytomegalovirus replication

Abstract: Valproic acid (VPA), a simple branched-chain fatty acid having anticonvulsant activity and used in the treatment of many forms of epilepsy, markedly stimulated human cytomegalovirus (HCMV) replication in human fibroblasts (MRC-5 cells). The maximum level of stimulation was reached when cells were treated for 24 h before infection. The enhancement of virus replication correlated with an increase in the number of immediate early (IE) and early (E) antigen-positive cells. VPA also induced expression of IE antigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 40 publications
2
28
0
Order By: Relevance
“…A recent study has suggested that initially, upon infection, viral IE promoters become associated with an active chromatin configuration, whereas early and late promoters become associated with repressive chromatin and, as infection proceeds, dynamic changes in the chromatin structure of these early and late gene promoters occurs Kuntz-Simon & Obert, 1995;Michaelis et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has suggested that initially, upon infection, viral IE promoters become associated with an active chromatin configuration, whereas early and late promoters become associated with repressive chromatin and, as infection proceeds, dynamic changes in the chromatin structure of these early and late gene promoters occurs Kuntz-Simon & Obert, 1995;Michaelis et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has suggested that initially, upon infection, viral IE promoters become associated with an active chromatin configuration, whereas early and late promoters become associated with repressive chromatin and, as infection proceeds, dynamic changes in the chromatin structure of these early and late gene promoters occurs (Cuevas-Bennett & Shenk, 2008). However, evidence from studies using murine CMV (MCMV) have shown that addition of the histone deacetylase (HDAC) inhibitor trichostatin A (TSA) to permissive cells increases the levels of murine IE1 gene expression (Tang & Maul, 2003) and, tellingly, others have shown that treatment of human fibroblast or epithelial cells with the pan-specific HDAC inhibitor valproic acid also increases viral IE late gene expression (Kuntz-Simon & Obert, 1995;Michaelis et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…on May 12, 2018 by guest http://jvi.asm.org/ alone or in the presence of another HDAC inhibitor which activates HCMV gene expression, VPA (46,59,60), and determined the percentage of IE1-positive nuclei. As expected, there were essentially no IE1-positive cells in undifferentiated monocytes.…”
Section: Vol 81 2007 Hcmv Uses Daxx Defense For Latent-like Infectimentioning
confidence: 99%
“…In addition, VPA can induce the demethylation of exogenous plasmid DNA in mammalian cells (26). VPA has been previously shown to activate lytic viral gene expression in cells infected with human cytomegalovirus or KSHV (27)(28)(29). We therefore reasoned that VPA treatment might induce lytic EBV gene expression in latently infected host cells and/or enhance the ability of chemotherapy to activate lytic EBV gene expression in EBV-infected tumor cells.…”
Section: Introductionmentioning
confidence: 99%